2001
DOI: 10.1046/j.1523-1739.2001.99200.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Matrix Effects on Pond Occupancy in Newts

Abstract: In farmlands, the population viability of many amphibians is suspected to depend on the resistance the matrix of crop fields presents to movements between ponds and terrestrial sires and movements among ponds. Over recent decades the increase in cereal grouping at the expense of cattle breeding has caused a drastic change in habitat matrix in many European regions. We investigated the effect of such change on populations of three newt species (Triturus helveticus, T. alpestris, and T. cristatus) by comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
161
4
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(181 citation statements)
references
References 58 publications
11
161
4
5
Order By: Relevance
“…Because the distribution and movement patterns of amphibians can depend on matrix heterogeneity (Joly et al 2001, Stevens et al 2004, Mazerolle and Desrochers 2005, Rittenhouse and Semlitsch 2006, we also evaluated support for different models of connectivity. Desiccation risk has been identified as an important cost of movement for juvenile dispersers due to their small bodies, permeable skin, and high surface-area-to-volume ratio compared to adults (Spight 1968, Rothermel andSemlitsch 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because the distribution and movement patterns of amphibians can depend on matrix heterogeneity (Joly et al 2001, Stevens et al 2004, Mazerolle and Desrochers 2005, Rittenhouse and Semlitsch 2006, we also evaluated support for different models of connectivity. Desiccation risk has been identified as an important cost of movement for juvenile dispersers due to their small bodies, permeable skin, and high surface-area-to-volume ratio compared to adults (Spight 1968, Rothermel andSemlitsch 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As far as breeding sites are concerned, the Montenegrin karst newts' aquatic preferences overall appear to fit into the general picture of the "preferable" newt breeding site (a water body with a relatively stable hydroperiod, with dense aquatic vegetation, intermediate pH, and ionic concentration, and without fish) (e.g., Arntzen & Teunis 1993;Ildos & Ancona 1994;Marnell 1998;Oldham et al 2000;Babik & Rafinski 2001;Joly et al 2001;Denoël et al 2005;Skei et al 2006;Denoël & Lehmann 2006). However, regarding the aquatic preferences of new species in the Montenegrin karst area, none of the breeding site characteristics could discriminate newt species, both in syntopy and allotopy.…”
Section: Discussionmentioning
confidence: 94%
“…The quality and quantity of these factors partially determine the presence of populations to the extent that some features can be isolated as of particular diagnostic importance and used as a basis for determining the likelihood of newt occurrence (e.g., Oldham et al 2000). Landscape characteristics, such as the density of nearby water bodies and the possible network of migration corridors (e.g., Joly 2001;Van Buskirk 2005), are very important because newts exhibit limited dispersal abilities, spawning-site fidelity and structuring as demes (Arntzen & Wallis 1991;Ficetola & Bernardi 2004;Smith & Green 2005;Jehle & Sinsch 2007). However, understanding of the newt-speciesdistribution causalities has been largely improved using spatial-environmental modeling of environmental characteristics in studies aimed at elucidating problems such as the determination of a species' range limits, the definition of the biogeographical history of species, and the impact of climate warming (e.g., Teixeira et al 2001;Teixeira & Arntzen 2002;Arntzen 2006;Skei et al 2006;Arntzen & Themudo 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous ecological modeling showed that paedomorphs are primarily favoured in deep and oxygenated waters . It is also likely that abundances depend on the size of wetlands (Joly et al 2001). Because previous ecological modeling showed the low effect of terrestrial variables on the distribution and abundance of paedomorphic palmate newts in Larzac (Denoël andFicetola 2014, 2015), only aquatic variables were taken into account in this study.…”
Section: Habitat Featuresmentioning
confidence: 99%